2014
DOI: 10.1007/s00259-014-2824-5
|View full text |Cite
|
Sign up to set email alerts
|

The evidence base for the use of internal dosimetry in the clinical practice of molecular radiotherapy

Abstract: Molecular radiotherapy (MRT) has demonstrated unique therapeutic advantages in the treatment of an increasing number of cancers. As with other treatment modalities, there is related toxicity to a number of organs at risk. Despite the large number of clinical trials over the past several decades, considerable uncertainties still remain regarding the optimization of this therapeutic approach and one of the vital issues to be answered is whether an absorbed radiation dose-response exists that could be used to gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(139 citation statements)
references
References 54 publications
1
131
1
6
Order By: Relevance
“…They recommended collecting data on several parameters to construct a patient-specific treatment plan, taking into account various patient-specific characteristics to predict the probability of response and predisposition to toxicity. Dosimetry can be used as a predictor of therapy response and toxicity; a relationship between tumor-absorbed dose and response has already been demonstrated for 90 Y-DOTATOC (23).…”
Section: Innovative Methods As Predictors Of Therapeutic Responsementioning
confidence: 99%
“…They recommended collecting data on several parameters to construct a patient-specific treatment plan, taking into account various patient-specific characteristics to predict the probability of response and predisposition to toxicity. Dosimetry can be used as a predictor of therapy response and toxicity; a relationship between tumor-absorbed dose and response has already been demonstrated for 90 Y-DOTATOC (23).…”
Section: Innovative Methods As Predictors Of Therapeutic Responsementioning
confidence: 99%
“…As has been stated in a recent review article on the evidence base for the use of internal dosimetry in the clinical practice of molecular radiotherapy by Strigari et al [3], this evidence implies a correlation between the absorbed doses delivered and the response and toxicity, indicating that dosimetry-based personalized treatments would improve outcome and increase survival.…”
mentioning
confidence: 84%
“…Despite a correlation between absorbed doses and treatment response and toxicity [9], all evidence supporting a dose response relationship from dosimetry in 90 Y-RE is based on either non-controlled prospective or retrospective studies.…”
Section: Dose Response Relationshipmentioning
confidence: 99%
“…A recent review by the EANM Dosimetry Committee identified 48 papers (out of 79 surveyed) employing the use of radionuclide dosimetry showing a strong correlation between absorbed dose and the tumour response & toxicity over a wide range of radionuclide treatments (including 90 Y-RE) [9], and many works have noted the lack of randomized trials comparing dosimetry-based radionuclide therapy to fixed dosing, or dosing per kg body weight [10,11]. For routine use, there is a requirement of standardized procedures for absorbed dose calculations [12] and improved reliability of radiobiological models used to convert dosimetric data to biologic endpoints [13].…”
Section: Introductionmentioning
confidence: 99%